Local habitat disturbance increases bird nest predation in the Brazilian Atlantic rainforest - Rodrigues, V. B.; Jesus, F. M.; Campos, R. I. (Animal Biodiversity and Conservation, 2018)
We evaluated the effect of anthropogenic disturbance on nest predation in Brazilian Atlantic forest. Artificial nests were distributed in fragments with distinct degrees of anthropogenic disturbance. We found a higher proportion of egg predation on the ground and in the fragments classified as ‘high’ and ‘medium’ disturbance than in the fragments classified as ‘low’ degree of disturbance. The higher egg predation is probably linked to low structural complexity of vegetation and high accessibility of these areas to opportunistic predators. We suggest that forest fragments with high vegetation complexity and low human activity should be preserved in order to maintain the biodiversity of bird species.